Analysis challenges of Engineering, Procurement, Construction and Commissioning (EPCC) contract of East Coast Rail Link (ECRL) using principal component analysis method - NORAZMI HANIF BIN SUKAIMI; Joewono Prasetijo; Mohd Azan Ibrahim (Progress in Engineering Application and Technology, 2024)
This thesis examines the key challenges of Engineering, Procurement, Construction, and Commissioning (EPCC) contracts in Malaysia’s East Coast Rail Link (ECRL) project. It identifies these challenges, proposes solutions, and evaluates the sustainability of EPCC contracts through a mixed-method approach. A survey of key stakeholders and Principal Component Analysis (PCA) revealed main challenges such as design changes, cost overruns, stakeholder interdependence, regulatory compliance, technical integration, and timeline delays. Solutions include better project management, improved communication, advanced technologies, and strong regulatory frameworks. The study compares EPCC with Design-Build (DB) and Design-Bid-Build (DBB) methods, highlighting that while EPCC offers integrated management and cost benefits, it demands rigorous coordination for sustainability. The findings provide insights for policymakers, practitioners, and researchers on managing large-scale infrastructure projects sustainably with EPCC contracts.